Left Ear Hearing Predicts Functional Activity in the Brains of Patients with Alzheimer's Disease Dementia. (April 2021) - Aylward, Alana; Naidu, Susan R.; Mellum, Catherine; King, Jace B.; Jones, Keith G.; Anderson, Jeffrey S.; Foster, Norman L.; Gurgel, Richard K.
Objectives: To determine whether central speech processing ability, as measured by hearing in noise, differs between right and left ears in adults with Alzheimer's disease related dementia (AD) as well as whether differences in central speech processing ability correlate with an fMRI-based measurement of global functional brain connectivity. Methods: This prospective study was carried out at a tertiary referral center. Patients with an AD diagnosis and pure tone averages 40 dB HL or better were included. They were examined using resting-state fMRI and underwent central audiometric testing using the Dichotic Sentence Identification Test (DSI), the Dichotic Digits Test (DD), and the Synthetic Sentence Identification Test (SS), which test hearing in noise. DSI scores were correlated with resting-state fMRI connectivity between 361 distinct gray matter brain regions of interest (ROIs). Average global connectivity was calculated as mean functional connectivity between an ROI and the other 360 regions, a quantitative marker representing overall functional connectivity in the brain. Results: Sixteen subjects had adequate fMRI and hearing data. The average age was 71.5 years old (±6.0). The average DSI score for the left ear was 40% (±34%) compared to 90% (±10%) in the right ear ( P < .001). No difference between ears was noted on the DD. SS does not differentiate between ears, but worsening scores were noted with increasing background noise. Of the fMRI ROIs, 269 of the 361 had multiple comparison corrected significant correlations between global connectivity and DSI of the left ear ( P = .004, r = .673), and all 269 showed higher functional connectivity for individuals with higher left DSI score. No correlations between DSI of the right ear and functional connectivity were found. Conclusions: Correlation was noted between left sided DSI and functional connectivity in patients with AD. Auditory input from the left ear was more susceptible to impairment, suggesting that side-specific auditory input may influence central auditory processing.